MULTIPLE CORRELATION OF READING PERCEPTION AND READING INTEREST TO READING HABIT DURING THE PANDEMIC COVID-19 IN THE JUNIOR HIGH SCHOOL - Saitri, I Gusti Ayu Ditha; Tantra, Dewa Komang; Agustini, Dewa Ayu Eka (Universitas Pendidikan Ganesha, 2021)
There are still many students who have low reading comprehension. This is because students are less interested in reading. In addition, students also do not have the habit of reading, which affects students’ abilities. This study aims to analyze the dual relationship between reading perception, reading interest, and students’ reading habits during the Covid-19 pandemic. EFL learning is carried out through an online platform, namely Google Classroom. The population of this study was the seventh-grade students who found 70 students. The design used is a quantitative research design. Data was collected using the Reading Perception Scale, Reading Interest Scale, and Reading Habits Scale. Data were analyzed descriptively and inferentially using Multiple Correlations from a combination of predictor variables and criteria. The results showed that the students’ reading perception was moderate; moderate reading interest; sensible reading habits; and four the double correlation of reading perception and reading interest on reading habits proved to have a significant and high positive correlation (R = 0.851 with = 0.01). This research implies that students need to improve their reading experience, reading motivation, time spent reading, and frequent reading activities. This also has implications for EFL teachers to provide learning materials and appropriate learning approaches/methods/techniques in reading skills.